The Multi-level Factors Affecting the Public Mind of Students in Primary Schools under the Offices of Primary Educational Service Area in the Northeast of Thailand - Lakmee, Nualprang; Pongpinyo, Phongnimit; Sroinam, Somkid (Dhammathas Academic Journal, 2023)
The purpose of this research are to 1) study the students’ public mind level in Primary Schools under the Offices of Primary Educational Service Area in the Northeast of Thailand, 2) study the student-level, class-level and school-level factors that affect the students’ public mind and 3) construct a multi-level model of factors affecting students’ public mind. This research is quantitative research. The sample comprises 48 administrators, 96 teachers and 1,440 students selected through multi-stage sampling. The research instruments are questionnaires, and data analysis uses percentage, mean, and standard deviation. The multi-level model is analyzed using HLM8.2. The research results find that: 1. The public mind of students under the Offices of Primary Educational Service Area in the Northeast of Thailand is at the highest level. 2. Regarding student factors find that the parenting of parents, the attitude toward public mind, and the perceived self-efficacy affecting the students’ public mind are statistically significant at the .01 level, while social support is statistically significant at the .05 level. Regarding classroom factors find that teachers’ behavior, the learning and teaching environment, the teaching quality by the teachers, and the relationship between teachers and students affected the students’ public mind at the .05 level of statistical significance. With regard to school factors find that school support significantly affected the students’ public mind at the .01 level. 3. The multi-level model of factors affecting the students’ public mind is illustrated below: PUBLIC = 4.606 + 0.156PARE*CLIM + 0.117ATTI*CLIM + 0.400ATTI*BEHA + 0.385ATTI*TEACH + 0.540CAPA*BEHA + 0.531CAPA*TEACH + 0.077SUPP + 0.157BEHA + 0.076ENVI + 0.161TEACH + 0.78RELA + 0.261PARE + 0.245ATTI + 0.063CAPA + 0.070SOCI